A second paradigm for gene activation in bacteria. (25th October 2006) - Buck, M.; Bose, D.; Burrows, P.; Cannon, W.; Joly, N.; Pape, T.; Rappas, M.; Schumacher, J.; Wigneshweraraj, S.; Zhang, X.
Abstract : Control of gene expression is key to development and adaptation. Using purified transcription components from bacteria, we employ structural and functional studies in an integrative manner to elaborate a detailed description of an obligatory step, the accessing of the DNA template, in gene expression. Our work focuses on a specialized molecular machinery that utilizes ATP hydrolysis to initiate DNA opening and permits a description of how the events triggered by ATP hydrolysis within a transcriptional activator can lead to DNA opening and transcription. The bacterial EBPs (enhancer binding proteins) that belong to the AAA + (ATPases associated with various cellular activities) protein family remodel the RNAP (RNA polymerase) holoenzyme containing the σ 54 factor and convert the initial, transcriptionally silent promoter complex into a transcriptionally proficient open complex using transactions that reflect the use of ATP hydrolysis to establish different functional states of the EBP. A molecular switch within the model EBP we study [called PspF (phage shock protein F)] is evident, and functions to control the exposure of a solvent-accessible flexible loop that engages directly with the initial RNAP promoter complex. The σ 54 factor then controls the conformational changes in the RNAP required to form the open promoter complex.